Saccharomyces cerevisiae hydrolyzate: its effect on the in vitro ruminal microbial population of star grass (cynodon nlemfuensis) - Galindo, Juana; González, Niurca; Marrero, Yoandra; Rodríguez, Marlen; Herrera, Magaly (Cuban Journal of Agricultural Science, 2024)
An experiment was carried out with the hydrolyzate of Saccharomyces cerevisiae, registered as PROBIOLEV®, obtained in Cuba from the hydrolysis of distillery cream from the enzymatic crude of Bacillus subtilis E-44, to determine its effect on the ruminal microbial population of star grass (C. nlemfuensis). The in vitro gas production technique was applied, with modifications according to the proposed objective. Three treatments were established: A) star grass control, B) star grass + yeasts cream and C) star grass + yeasts hydrolyzate. The doses of cream and hydrolyzate were 100 mL/kg of concentrate/day, equivalent to 130 mg of (β 1.3) glucan/kg of concentrate. Samplings were done before incubation, and at 3 and 6 hours after incubation. The hydrolyzate activated the total bacterial populations (P=0.0088) by 62 %, which corresponds to 19.36 x 1011 CFU/mL more of bacteria, which means an increase in bacterial biomass. Cellulolytic bacteria were more numerous (P=0.0042) and the total number of cellulolytic fungi increased (P=0.0009) with the hydrolyzate. There was no effect of time on the total viable bacteria, cellulolytic bacteria and cellulolytic fungi. It is concluded that the hydrolyzate produces changes in the ruminal population, increasing the population of total viable bacteria, bacteria and cellulolytic fungi, an event that could favor the degradation of the fiber contained in the star grass.